A Method of Fitting BOTDA Data for the Estimation of the Brillouin Frequency Shift - Komodromos, Michael; Polycarpou, Alexis; Ioannou, Andreas; Argyrou, Maria C.; Kalli, Kyriacos (My University, 2023)
A Brillouin Optical Time-Domain Analysis (BOTDA) Lorentzian data fitting method to estimate the Brillouin Frequency Shift (BFS) at successive locations along the length of the sensing optical fiber is proposed. The data used to test the method is obtained from an experimental setup built to conduct temperature and strain measurements. Before Lorentzian fitting the noisy data is averaged and filtered. The proposed method attempts to lower computational complexity in determining the BFS at each location by using the resulting parameters of a completed Brillouin gain spectrum (BGS) curve-fitting as initial set of parameters for the next location BGS fitting. Completion of the Lorentzian fittings using the Levenberg-Marquardt nonlinear curve fitting algorithm is achieved in a smaller number of iterations, improving the performance in obtaining the BFS.
Keywords: BFS estimation; BOTDA; Levenberg-Marquardt algorithm (LMA); Lorentzian fitting